Religious Governance and Structural Da’wah: Institutional Transformation of Indonesia’s Ministry of Religious Affairs in Public Policy Perspective - Rahmat Ramadan; Fitrah Amaliah Hasibuan; Muhammad Firdaus; M. Yakub (Islam and Social Sciences Review, 2025)
This study examines the institutional transformation of Indonesia’s Ministry of Religious Affairs (Kementerian Agama Republik Indonesia) within the framework of public policy and structural da’wah in response to the evolving socio-political and religious dynamics of Indonesian society. Employing a qualitative approach through document analysis and library research, this study analyzes government regulations, academic literature, policy documents, and previous scholarly studies related to religious governance, religious moderation, and state-religion relations in Indonesia. The findings reveal that the Ministry of Religious Affairs has experienced a significant paradigm shift from a predominantly administrative and doctrinal institution toward a more dialogical, inclusive, and service-oriented religious bureaucracy. In this context, religious policies such as religious moderation programs, zakat and waqf governance, halal assurance, and community religious development function not only as instruments of state regulation but also as mechanisms of structural da’wah aimed at strengthening social cohesion and public welfare. However, the implementation of these policies continues to face several structural challenges, including bureaucratization of religion, political intervention, institutional fragmentation, and declining public trust in religious institutions. This study contributes to the discourse on religious governance by highlighting the complex interaction between religion, state authority, and public policy in contemporary Indonesia. The study further argues that strengthening transparent, participatory, and collaborative governance is essential to enhancing the effectiveness of religious policy and promoting inclusive religious development in a pluralistic society.